Enhancing Mini Greenhouse Design: A CFD Analysis of Temperature, Humidity, and Wind Flow Distribution - Putri, Irriwad; Aldi, Rahmah Tasya; Hasan, Ashadi (The University of Lampung, 2024)
Research has been carried out on simulating the distribution of temperature, humidity and wind direction in a mini greenhouse using CFD ansys with several fan speed variations. This study aims to simulate the microclimate in a mini greenhouse, namely in the form of temperature, humidity and wind direction with variations in fan speed, namely with speeds of 1.7 m/s, 2.0 m/s and 2.2 m/s. Field measurement data regarding temperature, humidity (RH) in the tunnel-type mini greenhouse that has been carried out is used as input or input to the boundary conditions in the CFD mini greenhouse simulation. The results of the mini greenhouse CFD simulation using Ansys FLUENT are shown in the form of contour images of each condition. Temperature distribution contour, the humidity distribution contour (RH) and the airflow velocity distribution contour indicated by the vector will be used as the focus of this research. The numerical simulation shows quite good results when compared with the results of measurements in the field with the maximum error value obtained, which is 4.04%. Keywords: Computational Fluid Dynamics, Humidity, Simulation, Temperature, Wind direction.